CHALLENGES IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Munavvar Umarova; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Learning English as a foreign language has become an essential skill in today’s globalized world. Many learners face various difficulties while acquiring the language, including linguistic, psychological, and environmental challenges. This paper discusses the most common challenges students encounter and suggests possible solutions to improve English language learning.